Effects of Tribulus terrestris and Basella alba Extract on Sex Reversal on Poecilia reticulata - Anjana, Ashokan; Raja , Selvaraju (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study examined the effects of Tribulus terrestris and Basella alba on sex reversal in the guppy, Poecilia reticulata. This study aimed to introduce a new environmentally friendly method for masculinization in P. reticulata. Since male guppy has higher commercial value than females. T. Terrestris (ET) and Basella alba (EB) are a natural, non-toxic herb that helps enhance testosterone levels in humans and animals. Different concentrations (0.0, 5.0, 10.0, and 15.0 g L-1) of ET and EB were investigated for sex reversal in P. reticulata. The plant extracts were administered by immersion of newly hatched offspring once a week for two months. The dosage of 15.0, g L-1 ET was the most effective dosage that ensured a maximum male ratio (82.0, p<0.01). Although, sex ratios of fish in treatment 5.0 and 10.0 g L-1 ET were not significantly different from the expected 1:1 ratio, in these two groups treatment with ET and EB also resulted in a higher number of males (71.9 and 61.1; 82.0 and 78.5, respectively), than control (p>0.05). Total survival rates in all treatments and control were uniformly high ranging from 92% and 97% (p>0.05). It is concluded that ET has no negative effect on the survival rate of P. reticulata. All groups of ET-treated fish exhibited growth acceleration compared to the control group, but only ET treatment at the concentration of 15 and 10 g L-1 ET significantly improved growth rate of P. reticulata (p<0.01). Histological examinations revealed that the testes of fish treated with ET and EB extract contained all stages of spermatogenesis. Sex reversal in P. reticulata demonstrated that ET and EB-treated progenies showed successful sex reversal, spermatogenesis, and better growth rate than untreated progenies.